MITIGASI PERBANKAN SYARIAH DALAM PENCEGAHAN PENCUCIAN UANG BAGI PENDANAAN TERORISME - Hastuti, Luthfiyah Trini (Fakultas Hukum Universitas Sebelas Maret, 2013)
The study of terrorism later became one of the strategic issues are widely discussed in various circles , something that is very crucial because it relates to the sovereignty of a country . In a commission meeting in Conference All 23 ASEANAPOL in Manila , it was revealed that the current international authorities highlight Indonesia, Malaysia , and the Philippines due to a number of suspects have already started collecting humanitarian aid and has ties to terrorist organizations . Indonesia should pay full attention to correct weaknesses in meeting the nine special recommendations of the FATF (Financial Action Task Force on Money Laundering ) Terrorist Financing because the evaluation result Mutual Evaluation ( ME ) , handling counter-terrorism financing in Indonesia is considered still weak . Mitigation form of Islamic banking can be done in tackling the entry and exit of the flow of funds to terrorist activities can be done with the one used to identify the typology of perpetrators of crimes of terrorism . In addition to consistently do what is mandated in No.11/28/PBI/2009 Bank Indonesia Regulation on the Implementation of Anti -Money Laundering and Combating the Financing of Terrorism for Commercial Banks.